A NEW FUZZY HYBRID MCDM-ZOGP APPROACH FOR PRODUCT SELECTION PROBLEM: A CASE STUDY OF THE FIBER OPTIC CABLE - Karadağ, İlker and kılıç delice, elif (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The product selection is often a complicated and time process for both designers and engineers due to the presence of a large number of products with diverse properties. It is a fuzzy multi criteria decision making (MCDM) process involving both multiple criteria, which are dependent, and uncertain data which usually results from customer’s lack of knowledge about the product. This study aims to propose a novel fuzzy MCDM- Zero One Goal Programming (ZOGP) approach considering dependence among criteria for product selection in a fuzzy environment. In this approach, the fuzzy MCDM method consisting of fuzzy DEMATEL and fuzzy VIKOR&GRA is developed to obtain priorities of alternatives, which are then used to construct a ZOGP model which provides a solution considering both weights of objectives and the priorities of alternatives, as distinct from traditional ZOGP. The proposed approach is illustrated using a real-world applicaiton in the Turkish fiber optic cable industry.